Antibodies to ribosomal P proteins of Trypanosoma cruzi in Chagas disease possess functional autoreactivity with heart tissue and differ from anti-P autoantibodies in lupus - Kaplan, Dan (The National Academy of Sciences of the USA, 1997)
Anti-P antibodies present in sera from patients with chronic Chagas heart disease (cChHD) recognize peptide R13, EEEDDDMGFGLFD, which encompasses the C-terminal region of the Trypanosoma cruzi ribosomal P1 and P2 proteins. This peptide shares homology with the C-terminal region (peptide H13 EESDDDMGFGLFD) of the human ribosomal P proteins, which is in turn the target of anti-P autoantibodies in systemic lupus erythematosus (SLE), and with the acidic epitope, AESDE, of the second extracellular loop of the β(1)-adrenergic receptor. Anti-P antibodies from chagasic patients showed a marked preference for recombinant parasite ribosomal P proteins and peptides, whereas anti-P autoantibodies from SLE reacted with human and parasite ribosomal P proteins and peptides to the same extent. A semi-quantitative estimation of the binding of cChHD anti-P antibodies to R13 and H13 using biosensor technology indicated that the average affinity constant was about 5 times higher for R13 than for H13. Competitive enzyme immunoassays demonstrated that cChHD anti-P antibodies bind to the acidic portions of peptide H13, as well as to peptide H26R, encompassing the second extracellular loop of the β(1) adrenoreceptor. Anti-P antibodies isolated from cChHD patients exert a positive chronotropic effect in vitro on cardiomyocytes from neonatal rats, which resembles closely that of anti-β(1) receptor antibodies isolated from the same patient. In contrast, SLE anti-P autoantibodies have no functional effect. Our results suggest that the adrenergic-stimulating activity of anti-P antibodies may be implicated in the induction of functional myocardial impairments observed in cChHD.